FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PENINGKATAN KARIR PEGAWAI NEGERI SIPIL PEMERINTAHAN KOTA MAKASSAR - Nashriah Akil (AkMen JURNAL ILMIAH, 2016)
This study aims to identify and analyze the factors - factors that berepngaruh to increased career Civil Servant Government of Makassar. Data used in this study are primary data that the questionnaire answers of respondents with data analysis using multiple linear regression with SPSS 20. The sample in this study were 75 respondents Civil Servants in the scope of the Government of Makassar. The results of this study stated that based on the results of data analysis on demonstrating leadership style factors affect the 65.3% increase in employee career and motivation to work, this means that 34.7% (100% - 65.3%) increase in employee career is influenced by other factors outside research variables are also influential.